2018
DOI: 10.1021/acs.analchem.7b05309
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pressure on the Composition of Gaseous Reference Materials

Abstract: We have shown that the amount fraction of carbon dioxide in a nitrogen or synthetic air matrix stored in cylinders increases as the pressure of the gas mixture reduces, while the amount fraction of methane remains unchanged. Our measurements show the initial amount fraction of carbon dioxide to be lower than the gravimetric value after preparation, which we attribute to the adsorption of a proportion of the molecules to active sites on the internal surface of the cylinder and the valve. As the mixture is consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 13 publications
3
19
3
Order By: Relevance
“…After the second cleaning procedure (Table 1d) our results compared reasonably well with the low flow experiments reported in Schibig et al (2018) and Brewer et al (2018). The former setup consisted of higher volume cylinders, and they suggested no 10 difference between the coated and uncoated aluminum cylinders.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…After the second cleaning procedure (Table 1d) our results compared reasonably well with the low flow experiments reported in Schibig et al (2018) and Brewer et al (2018). The former setup consisted of higher volume cylinders, and they suggested no 10 difference between the coated and uncoated aluminum cylinders.…”
Section: Discussionsupporting
confidence: 89%
“…A significant difference between this study and the previous studies (Leuenberger et al, 2015;Brewer et al, 2018;Schibig et al, 2018) is the onset of adsorption effects. All previous studies have shown that for high pressure cylinders, usage below 20 bar is problematic.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…It is NPL practice not to use cylinders that show large initial losses due to concerns over what happens to that adsorbed material during the use of the cylinder. In a recent paper, Brewer et al (2018) have shown that at low pressures (<25 bar), desorption of previous adsorbed gases (carbon dioxide and hydrochloric acid) can affect the mole fraction of reference materials.…”
Section: Oxygenated Vocs (Ovocs)mentioning
confidence: 99%